Inhibition of Growth of Escherichia coli, Salmonella typhimurium, and Clostridia perfringens on Chicken Feed Media by Lactobacillus salivarius and Lactobacillus plantarum - Murry, A.C.; Hinton, A.; Jr.,; Morrison, H. (International Journal of Poultry Science, 2004)
Two dominant strains of lactobacilli isolated from a botanical probiotic were identified and evaluated to determine their ability to inhibit the in vitro growth of E. coli, S. typhimurium, and C. perfringens on a medium that simulated a normal starter and grower diet for broiler chickens. The two strains identified were Lactobacillus salivarius and Lactobacillus plantarum. In the inhibition assay in vitro, both strains of Lactobacillus from the probiotic inhibited (P < 0.001) growth of E. coli, S. typhimurium, and C. perfringens for both the starter and grower diets when compared to the control diets. Both strains of Lactobacillus for both the starter and grower diets produced more (P < 0.001) acetic and lactic acid than was found in the control diets. Also, the pH of the media with cultures of L. plantarum and L. salivarius for both the starter and grower diets was lower (P < 0.001) than for the control diets. These results indicate that L. salivarius and L. plantarum contained in the botanical probiotic can ferment carbohydrates in poultry feed to produce pH levels and concentrations of lactic and acetic acid that inhibit the growth of E. coli, S. typhimurium, and C. perfringens.